2021
DOI: 10.3390/ijms22010418
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia: Focus on Endothelial Damage as a Cause of Erectile Dysfunction

Abstract: Erectile Dysfunction (ED) is defined as the inability to maintain and/or achieve a satisfactory erection. This condition can be influenced by the presence of atherosclerosis, a systemic pathology of the vessels that also affects the cavernous arteries and which can cause an alteration of blood flow at penile level. Among the cardiovascular risk factors affecting the genesis of atherosclerosis, hyperhomocysteinemia (HHcys) plays a central role, which is associated with oxidative stress and endothelial dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
(27 reference statements)
0
15
0
2
Order By: Relevance
“…Homocysteine (HCY) can inhibit eNOS and promote NOS uncoupling, thereby reducing the production of endothelium‐dependent NO (Musicki et al., 2010). Currently, hyperhomocysteinaemia (HHcy) has also been recognised as an independent risk factor for vascular endothelial dysfunction and ED (Salvio et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Homocysteine (HCY) can inhibit eNOS and promote NOS uncoupling, thereby reducing the production of endothelium‐dependent NO (Musicki et al., 2010). Currently, hyperhomocysteinaemia (HHcy) has also been recognised as an independent risk factor for vascular endothelial dysfunction and ED (Salvio et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Also, studies have shown that hyperhomocysteinemia affects the formation and maintenance of a systemic inflammatory response. This was shown by biochemical blood tests of cardiac patients, where overestimated markers of inflammation (interleukin-6, fibrinogen, CRP) were clearly demonstrated [18].…”
Section: The Effect Of Hyperhomocysteinemia On the Cardiovascular Systemmentioning
confidence: 84%
“…Carotid IMT (cIMT) has been demonstrated to be associated with atherosclerosis, CVD [55,56], and erectile dysfunction. The latter is a precocious marker of endothelial dysfunction [57,58]. Indeed, subjects with erectile dysfunction present higher cIMT and lower FMD than controls, and these parameters may be improved upon vasodilation induced by treatment with phosphodiesterase 5 inhibitors [59][60][61][62].…”
Section: How To Measure Endothelial Dysfunction: Direct and Indirect mentioning
confidence: 99%